Production and optimization of raw starch degrading amylase and cellulase in solid state fermentation (SSF) of agricultural waste by aspergillus sp. - Nur Fatin Husna, binti Roslan (Universiti Malaysia Sarawak, UNIMAS, 2012)
Agricultural waste such as sago hampas, rice husk, pineapple waste and cassava waste were used as solid substrate on solid state fermentation for the production of amylase and cellulase. The aims of this project were to identify the best strain in production of amylase and cellulase enzymes and to determine the optimum condition for the production on both enzymes on solid state fermentation system. There were five important fermentation parameters being studied; temperature, size of inoculum, time of incubation, moisture content and pH of the medium. In this project, Aspergillus niger PAN1 was selected as the best strain capable of producing both enzymes at the highest level. The optimum condition on solid state fermentation for the production of amylase and cellulase was recorded at day 3 for amylase and day 6 for cellulase of time of incubation, respectively. The pH suitable for high enzymatic activity was at pH 5.5 for amylase and pH 7.5 for cellulase activity, respectively. The optimum temperature of 30oC showed the highest yield of amylase activity and the highest production of cellulase activity was at the temperature of 40oC, respectively. In addition, the optimum inoculates that produce highest production of both amylase and cellulase enzymes are at 107 of spore suspension/ml. The medium was further optimized with 70% of moisture content. The enzyme was extracted and assayed by using DNS method to determine the total amount of reducing sugar released.